PASTRY BASED ON FLOUR WITH SPECIFIC CHARACTERISTICS - O. Makarova; Kateryna Khvostenko; Nataliia Sokolova; Anastasia Fateeva; Karyne Avetisian (Zernovì Produkti ì Kombìkorma, 2022)
Preservation of initially high quality of the pastry based on the natural ingredients throughout their shelf-life is a major factor to ensure their competitiveness. One of the effective ways of solving this task is using the types of wheat flour with specific characteristics. Differential approach to the technological characteristics of flour, depending on baked goods types, makes it possible to ensure the stability of the technological process and the quality of the produced products without usage of inorganic improvers. Among the types of wheat flour with specific characteristics the flour of waxy wheat, the starch of which does not contain amylose, which plays an important role in the stealing of flour products, is to particular interest. The studies found that waxy wheat flour characterised with higher gassing power and water absorption compare with control. According to their technological characteristics it is suggested to use wheat flours with specific characteristics in the technology of yeast-containg cakes, hardtacks with lower sugar capacity. Flour of extra-soft wheat Oksana is characterized by low water absorption and weak gluten, which are desirable technological properties for the production of most types of confectionery dough. It was found that waffles and wafers based on extra-soft wheat Oksana flour are characterized with lower density and better porosity and texture compared with the control. It is shown that the use of waxy wheat flour and biscuit wheat flour in the technology of mentioned pastry types leads to the technological process intensification, stabilization of their rheological characteristics, product quality and their freshness without adding of improvers.